THE CORRELATION BETWEEN STUDENTS’ VOCABULARY MASTERY AND SPEAKING SKILL - Srifani Simbuka; Ahmad Mustamir Waris; Rizqika Fajriah Dano (Universitas Muhammadiyah Gorontalo, 2020)
AbstractThis research aimed to find out wheter there is a correlation between student’ vocabulary mastery and their speaking skill or not. The subject were 40 students from eleventh grade students (XI MIPA 2) of MAN Model 1 Manado. The design that applied in this research quantitative method. The data gained in this research by giving the students speaking and vocabulary test then analyzed using Pearson product moment correlation formula. Based on the finding with the analysis and calculation, it was fond that the rxy was 0,799. Referring to the table of product moment interrelation of was in the interval 0f 0,70 – 0,90 which means between variable X and Y stated a high correlation. According to the table of significant with the degree of freedom (df+ N-nr) is 38, the significance level 5% is .0,320 and 1 % is 0,413. By comparing the value, it showed that rxy is bigger that r1 (0,320 < 0,799 > 0,412). It means there is significant correlation between vocabulary mastery and speaking skill which proved hat student’ vocabulary master increases in line with their speaking skill. Keywords: correlation, vocabulary master, speaking skill